Restricting polygamy law in Kurdistan - Iraq: analytical study - Arif, Arif Ali (s.n, 2012)
This research aims to show the extent of harmony in the restricting polygamy to the Kurdistan Region - Iraq with Regard of the Islamic law, this research also seeks to demystify the issue of polygamy, which has become a weapon in the hands of the enemies of Islam to distort our religion. The Research will mainly follow, inductive approach, of the texts and the views of jurists restricting polygamy, in addition to the analytical approach, in analyzing texts and legal restriction on polygamy. Finally this study will complete with a set of recommendations that would address the issue of restricting polygamy in the light of contemporary reality.